Reconfigurable multiple beams forming method based on liquid crystal on silicon. (June 2023) - Zhuo, Rusheng; He, Xiaoxian; Wu, Liang; Wang, Xiangru; Huang, Yanwei; Gu, Dongmei; Liu, Kang; Wang, Pinghe; Chen, Jian; Tang, Fu; Xu, Xingxing
Highlights: we proposed a novel method to realize reconfigurable optical multi-beams (ROMB). It supports user-defined dynamic beam arrangement including arbitrary beam number, arbitrary angle, and arbitrary power occupancy rate. Practical scheme and experimental setup provide an innovative, reliable, and low-cost solution. It is consisting of a commercial spatial light modulator device of liquid crystal on silicon (LCOS)and a 4-f image system for precise spatial pixel alignment and co-modulation of amplitude and phase. The average relative error between the experiment and simulation is less than 6% and the practical pointing accuracy is higher than 93.164%, also the maximum beam number is limited by diffraction angle range. Abstract: With the purpose of meeting the increasing requirement of free-space optical networking, reconfigurable multiple beams are required from a single terminal. In this paper, we demonstrate the role of co-modulation of amplitude and phase on incident laser beam using such a liquid crystal spatial light modulator. It enables arbitrary beam number, arbitrary pointing angle, and power occupation with multiple beams of excellent performance on a relative error and standard derivation when using typical groups of examples. Both numerical simulations and experimental results are presented demonstrating reconfigurable multiple beams forming via liquid crystal on silicon.